Demographic consequences of a changing environment on a population of Trinidadian guppies (Poecilia Reticulata) - Veylit, L (2016)
Ecologists are interested in the complex relationships between populations and their environment. Feedbacks from ecological interactions can change the biotic and abiotic landscape, impacting numerous aspects of a population. Selective pressures on phenotypic traits from processes such as predation and intraspecific competition can change the structure of populations. Structured models can be used to predict how individual level processes can determine population level responses and build an overall understanding of population dynamics. When these models are structured by fitness related phenotypic traits, they can simultaneously be used to provide insights into phenotypic change. In this thesis, I explore ecological drivers of the population and body size dynamics of Trinidadian guppies (Poecilia reticulata) following a change in predation environment. I used individual based data to explore how the life history of individuals across size classes is determined by population density and size-dynamics in a varying environment. I (i) used a modelling approach to determine how much female body size, population density, and the interaction between body size and density explain the temporal variation in demographic rates of individuals (ii) parameterized and analysed a density-dependent Integral Projection Model to make predictions about population dynamics. This thesis contributes to our understanding of the factors that determine phenotypic trait dynamics and population demography in a seasonally fluctuating environment. Understanding how populations respond to environmental variation over the long term has important implications as anthropogenic forces rapidly disrupt seasonal dynamics, with serious consequences for populations.